Optimal single-dose epidural neostigmine for postoperative analgesia after partial hepatectomy - Zhong, Qiao Sheng (Indian J Pharmacol, 2014)
OBJECTIVE: Neostigmine can produce analgesia by acting on the spinal cord. This study was to determine the optimal single-dose of epidural neostigmine for postoperative analgesia after partial hepatectomy. PATIENTS AND METHODS: Twenty-six patients undergoing elective partial hepatectomy under general anesthesia combined with epidural block were studied. The dose of epidural neostigmine was determined using Dixon's up-and-down method, starting from neostigmine 100 μg with an interval of 25 μg. Thirty minutes after skin incision, a predetermined dose of neostigmine was injected via the epidural catheter. Each patient received 0.125% bupivacaine and fentanyl 2 μg/ml for patient controlled epidural analgesia (PCEA) after the operation. Assessment of analgesia quality was performed at 8 h and 24 h after the operation. RESULTS: The ED(50) of epidural neostigmine in combination with PCEA for satisfactory analgesia was 226.78 ± 33.20 μg. Probit analysis showed that the ED(50) and ED(95) of epidural neostigmine were 228.63 μg (95% CI = 197.95–299.77 μg) and 300.12 μg (95% CI = 259.44–741.65 μg), respectively. CONCLUSION: The ED(50) and ED(95) of epidural neostigmine in combination with PCEA for satisfactory analgesia after partial hepatectomy were 228.63 μg (95% CI = 197.95–299.77 μg) and 300.12 μg (95% CI = 259.44–741.65 μg).